2007
DOI: 10.1080/12265080701694561
|View full text |Cite
|
Sign up to set email alerts
|

Neural Network Based Models for Efficiency Frontier Analysis: An Application to East Asian Economies’ Growth Decomposition

Abstract: There has been a long tradition in business and economics to use frontier analysis to assess a production unit's performance. The first attempt utilized the data envelopment analysis (DEA) which is based on a piecewise linear and mathematical programming approach, whilst the other employed the parametric approach to estimate the stochastic frontier functions. Both approaches have their advantages as well as limitations. This paper sets out to use an alternative approach, i.e. artificial neural networks (ANNs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
(46 reference statements)
0
3
0
1
Order By: Relevance
“…Aside from the aforementioned integrated approach, a group of researchers has utilized ANN as an alternative to DEA, which again implies promising opportunities in this research arena. Insightful research outcomes are found from the literature (Angelidis and Lyroudi, 2006;Liao et al, 2007;Santin, 2008;Santín et al, 2004;Wang, 2003).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Aside from the aforementioned integrated approach, a group of researchers has utilized ANN as an alternative to DEA, which again implies promising opportunities in this research arena. Insightful research outcomes are found from the literature (Angelidis and Lyroudi, 2006;Liao et al, 2007;Santin, 2008;Santín et al, 2004;Wang, 2003).…”
Section: Literature Reviewmentioning
confidence: 99%
“…To compute the performance of the ith unit, the error (E i ) between the actual output (P Actual(i) ) and the output obtained from the best structure of ANFIS (P ANFIS×(i) ) should be calculated using Equation ( 1) (Delgado, 2005;Liao et al, 2007):…”
Section: Anfis-based Algorithmmentioning
confidence: 99%
“…Athanassopoulos and Curram first introduced the idea of the combination of neural networks (NNs) and DEA for classification and/or prediction. Other papers that presented the benefits of combining DEA and NN are Liu et al, Liao et al, Santin, Santin et al and Wang . Azadeh et al proposed a highly unique flexible ANN algorithm to measure and rank scores of Iranian steam power.…”
Section: Introductionmentioning
confidence: 99%